Intimate Partner Violence Experiences During COVID-19 Among Male Couples. Issue 15 (August 2022) - Walsh, Alison R.; Sullivan, Stephen; Stephenson, Rob
In addition to the growing morbidity and mortality related to the 2019 novel coronavirus (SAR-CoV-2) pandemic, social distancing measures during the pandemic may result in increased intimate partner violence (IPV). However, it is yet unknown if gay, bisexual, and other men who have sex with men (GBMSM)'s IPV risk has increased during this time. This article describes and analyzes IPV experiences during the COVID-19 pandemic in a sample of coupled-GBMSM in the United States. We hypothesized that pandemic-driven stressors would be associated with increased IPV prevalence and severity. A sample of 214 coupled men living in the US who had previously participated in HIV-related couple studies was surveyed in July-September 2020. Respondents reported demographic, sexual and substance use behaviors, and relationship characteristics. Surveys also collected data on pandemic-related life-changes (employment, substance use, COVID-19 illness). IPV victimization and perpetration were measured with the Gay and Bisexual Men Intimate Partner Violence scale and measured individually experienced or perpetrated violence, sexual, emotional, monitoring, or controlling behaviors, and if a given behavior was new and/or had changed in frequency during the pandemic. Reported prevalence and pandemic-related changes in victimization and perpetration were described. New or more frequent IPV victimization was modeled against employment, substance use changes, COVID-19 illness, and outside sexual partners (modified by a couple's sexual agreement). IPV perpetration prevalence was 15.17%, 34.44% of which was new or more frequent. Victimization prevalence was 14.95%, of which 46.88% was new or more frequent. After adjustment, outside sexual partners were associated with IPV among those with nonmonogamous sexual agreements; each outside sexual partner increased the odds of new or more frequent victimization by 70% ( OR = 1.70; 95% CI [1.16, 2.51]). Given this study's documented rise in IPV among a sample of coupled men, additional research into IPV predictors, interventions, and support strategies in GBMSM populations are warranted.